China live : two decades in the heart of the dragon - Chinoy, Mike. 4 0 16; 5 (Atlanta : Turner Publishing, 1997)
Reflections from a journalist tracing political and historical events in China since the 1970s looking at how the country has experienced periods of enlightenment, tension, and violence.
Publisher's Weekly;Booklist;Kirkus Review
Adult;Adult
Keywords: 2 -- 0; 6; 20; History;History;History.;History -- China;China;China;China -- 1976-;Tiananmen Square Incident, 1989.;Tiananmen Square Incident, 1989.; 2